Citrus Flatid Planthopper, Metcalfa pruinosa (Say) (Insecta: Hemiptera: Flatidae) - Frank W. Mead (EDIS)
True to its name, the citrus flatid planthopper, Metcalfa pruinosa (Say), is found on citrus, but also is found on a wide variety of woody plants, many of which are used in the ornamental trade. This planthopper seldom causes economic damage to most plants except to those weakened by some other factor such as freeze damage. The unsightly white, flocculent, waxy material made by the nymphs impairs the sales quality of affected plants, partly because buyers sometimes mistake these deposits for those of mealybugs or the cottony-cushion scale. This document is EENY-329 (originally published as DPI Entomology Circular 85), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: June 2004.